Implementation of Total Quality Management in Creating Competitive Advantage - Fauzi, Muchammad (Journal of Digital Marketing and Halal Industry, 2021)
Total Quality Management is an important business-level strategy because it can create a competitive advantage. This study aims to analyze the Effect of Total Quality Management on employee creativity, performance, and Competitive Advantage. This study examines Total Quality Management as a potential source of competitive advantage. This research shows that most features are generally related to Total Quality Management, such as quality training, process improvement, an open culture, employee empowerment, and executive commitment can produce benefits. This research is quantitative research using primary data. The statistical tool used is regression at a 5% significance level. The research results indicate that all hypotheses are accepted. It means that Total Quality Management affects employee's creativity, performance, and competitive advantage. In addition, based on the theory of competitive advantage, corporate resource-based theory, and system theory. It can be concluded that Total Quality Management can produce cost-based benefits or differentiation to encourage the success of Total Quality Management in achieving competitive advantage.